ALGORITHM OF EXAMINATION OF PATIENTS WITH CYSTS OF LATERAL REGION OF NECK - Ткаченко, П.І.; Rezvina, K.Yu. (World of Medicine and Biology, 2010)
Examination of 67 patients with cysts of lateral region of neck which included clinico-history data, ultrasonic research, the cytologic, histological, biochemical, immunohistochemical researches of tissue structures of formation and its contents is spent. On the basis of generalisation of the received results the diagnostic algorithm which application allows more precisely is developed, in a short time interval to carry out differential diagnostics of cysts lateral region of neck already at pre-hospital stage.